Intersection of Faith, Gender, and Emotion: Exploring Emotional Labor Among Muslim Female Academics in Pakistan - Waqas Ali Khan; Dr. Namra Shahzadi; Misbah Arshad (Journal of Peace, Development and Communication, 2024)
This research attempts to trail back the toll of Muslim women on the work who feel their emotions are being out for jobs that they are doing in Pakistani universities. In the context of Pakistan, where cultural and gender dynamics contribute to the teaching profession, understanding the implications of emotional labor in Muslim female educators is crucial. The objectives of the study were to determine the extent of emotional labor undergone by Muslim female teachers in Pakistani universities, to probe the correlation between emotional labor and job satisfaction among Muslim female teachers, to analyse the effect of emotional labor on burnout among Muslim female teachers, to uncover the organizational aspects that cause or alleviate the emotional labor experienced by Muslim female teachers and to assess the moderating effect of institutional support on the link between emotional labor and job satisfaction. Under the principles of quantitative research, data was collected from 50 Muslim female teachers from public and private universities in Pakistan using the purposive sampling technique. The study shows that emotional labor is the dominant factor which is responsible for the decrease in satisfaction with the job, meaning that high levels of emotional labor are associated with lower job satisfaction especially among the Muslim female teachers. Also, there is a positive and significant relationship between the two variables in the study, which concludes that the utilization of emotional labor in the teachers will lead to burnout, emotional exhaustion, depersonalization, and a diminished sense of personal accomplishment. A critical perceived factor that plays a significant role in the relationship between emotional labor and job satisfaction is institutional support. The study revealed that teachers in private universities who were emotionally laborious reported significantly greater levels of it than the public university counterparts, thus, it is probably related to the more strenuous work and the higher performance requirements at these private institutions.